2005
DOI: 10.1016/j.femsle.2004.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain fatty acid biosynthesis in a branched-chain amino acid aminotransferase mutant ofStaphylococcus carnosus

Abstract: Fatty acid biosynthesis by a mutant strain of Staphylococcus carnosus deficient in branched-chain amino acid aminotransferase (IlvE) activity was analysed. This mutant was unable to produce the appropriate branched-chain alpha-ketoacid precursors for branched-chain fatty acid biosynthesis from the amino acids valine, isoleucine, and leucine, and required the short branched chain acids 2-methylbutanoic acid or 2-methylpropanoic acid for growth in a defined medium. The isoleucine related metabolites, alpha-keto-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…It may involve changes in the fatty acid composition of the membrane by varying the length of acyl chains, number of double bonds or branching of acyl chains by methyl groups (Klein et al 1999). Branched chain amino acids (leucine, isoleucine and valine) participate, after their uptake, in oxidative deamination and subsequent decarboxylation reactions to act as precursors in anteiso-branched chain fatty acid synthesis (Kim Jung-Ja and Miura 2004;Beck 2005;Beck et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It may involve changes in the fatty acid composition of the membrane by varying the length of acyl chains, number of double bonds or branching of acyl chains by methyl groups (Klein et al 1999). Branched chain amino acids (leucine, isoleucine and valine) participate, after their uptake, in oxidative deamination and subsequent decarboxylation reactions to act as precursors in anteiso-branched chain fatty acid synthesis (Kim Jung-Ja and Miura 2004;Beck 2005;Beck et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…IlvC also links amino acid biosynthesis to acetolactate-acetoin metabolism, where pyruvate can be transformed into acetoin, thus allowing for the production of more neutral compounds with a higher pK a than that of lactic acid. Branched-chain amino acid ATases catalyze the final step of amino acid biosynthesis; however, due to their dual function, they can play a role in both the biosynthesis and catabolism of branched-chain amino acids (6,23). In their biosynthetic capacity, ATases catalyze the final step in the generation of bcAAs.…”
mentioning
confidence: 99%
“…The ilvE gene, encoding a branched-chain amino acid aminotransferase, has been shown to play an important role in bcFA synthesis by providing precursors for the fatty acid biosynthetic machinery. It has also been shown that a mutation in ilvE leads to a nutritional requirement for amino acids and a change in the catabolites produced from amino acid degradation (6). For Staphylococcus carnosus, an ilvE mutant was shown to lose ATase activity for branched-chain amino acids (42), demonstrating its role in amino acid catabolism.…”
mentioning
confidence: 99%
“…Also, S. epidermidis-derived virulence factors have been studied in S. carnosus, such as phenol-soluble modulin peptides (55), the methicillin resistance gene (71), and biofilm formation by the S. epidermidis-derived ica genes (29). Elements of the sugar phosphotransferase system (PTS) have been structurally analyzed (27,45,53), and specific pathways have been investigated (6). Many reports deal with the function and application of S. carnosus in the food industry (39,61).…”
mentioning
confidence: 99%